Composition of phytoplankton in the Puck Bay and the open Baltic Sea - Klaudia Świacka; Alicja Michnowska; Jakub Maculewicz; Izabela Przednowek; Iga Ogrodowczyk; Sebastian Kozic (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2017)
The Puck Bay is an area characterised by specific hydrodynamic conditions that determine the distribution and composition of phytoplankton. The aim of this study was to investigate the differences in the phytoplankton composition and the content of photosynthetic pigments between the Puck Bay and open Baltic Sea. The material was collected from four stands which were localised in the inner and outer part of Hel Peninsula. In this study, it has been demonstrated that the composition of individual species of phytoplankton differed between stands in the inner and outer part of the Puck Bay. This investigation has also shown that the number of phytoplankton taxa was similar in three stands and it was much lower on the last stand (Stand 4). The differences in the concentration of photosynthetic pigments between all stands have also been observed.